Variation in yellow pigment content in bread (Triticum aestivum) and durum (Triticum turgidum var durum) wheat and synthetic hexaploids: genetic and environmental effects - RAM, SEWA; PATHANIA, MINAKSHI; TYAGI, BHUDEVA S (The Indian Journal of Agricultural Sciences, 2026)
Four hundred and ten genotypes representing Indian wheat varieties, selected germplasm lines, synthetic hexaploids and durum wheats were used in the present investigation to explore variability in yellow pigment content (YPC) in both bread (Triticum aestivum L.) and durum (Triticum turgidum Lvar durum) wheats. Microlevel test utilizing 0.2 g of the flour was developed to measure YPC in this investigation. There was strong correlation (R2=0.97) between values of YPC measured using microlevel test and AACC method. The data demonstrated large variation in YPC varying from 3.58 to 11.06 ppm with the average value of 7.08 ppm in durum wheats and 0.87 to 5.30 ppm with the average value of 3.19 ppm in bread wheat. Among bread wheat varieties, 1B/1R translocation lines showed statistically significant higher YPC as compared to non 1B/1R translocation lines (P<0.001). Sixteen advanced genotypes of bread wheat and 15 genotypes of durum wheat separately grown over four locations in North Western Plains Zones in India showed significant differences between means of YPC for genotypes, locations and also had interaction effect. The heritability of YPC was 0.79 in bread wheat and 0.72 in durum wheat. High heritability and large variations in YPC have great utility in improving end-product quality in wheat. Microlevel tests developed in the present investigation can assist in capturing larger numbers of QTLs indirectly during advancing the segregating lines in the breeding programme.